Prognostic factors influencing outcomes in hepatocellular carcinoma patients undergoing selective internal radiation therapy - Maria Stella Franzè; Paul Vigneron; Anna Sessa; Carlo Saitta; Julia Chalaye; Vania Tacher; Alain Luciani; Hélène Regnault; Ancuta Bejan; Rami Rhaiem; Daniele Sommacale; Vincent Leroy; et al. (Annals of Hepatology)
Selective internal radiation therapy (SIRT) has emerged as a viable endovascular treatment strategy for hepatocellular carcinoma (HCC). According to the Barcelona Clinic Liver Cancer (BCLC) classification, SIRT is currently recommended for early- and intermediate-stage HCC that is unsuitable for alternative locoregional therapies. Additionally, SIRT remains a recommended treatment for patients with advanced-stage HCC and portal vein thrombosis (PVT) without extrahepatic metastasis. Several studies have shown that SIRT is a versatile and promising treatment with a wide range of applications. Consequently, given its favourable characteristics in various scenarios, SIRT could be an encouraging treatment option for patients with HCC across different BCLC stages. Over the past decade, an increasing number of studies have focused on better understanding the prognostic factors associated with SIRT to identify patients who derive the most benefit from this treatment or to refine the optimal technical procedures of SIRT. Several variables can influence treatment decisions, with a growing emphasis on a personalised approach. This review, based on the literature, will focus on the prognostic factors associated with the effectiveness of radioembolization and related complications. By comprehensively analysing these factors, we aimed to provide a clearer understanding of how to optimise the use of SIRT in managing HCC patients, thereby enhancing outcomes across various clinical scenarios.